KEMAMPUAN MEMBACA PUISI PESERTA DIDIK KELAS IIA SDN 1 KARANGSARI KABUPATEN BANYUWANGI DI ERA NEW NORMAL - Noer, Fadhilah Noer Zannah (Perspektif Ilmu Pendidikan, 2022)
Abstract: The background of this research was finding out of students who had not have the ability of reading poetry well. This research aimed (1) to describe IIA grade students' reading poetry ability of SDN 1 Karangsari, Banyuwangi, in new normal era, and (2) the factors that affect IIA grade students' reading poetry ability of SDN 1 Karangsari, Banyuwangi, in new normal era. The type of this research was qualitative descriptive research. The subject of this research was IIA grade students of SDN 1 Karangsari, Banyuwangi, academic year 2021/2022 consisting of 22 students in the class. The research method used was interview and observation. The technique of data analysis used was qualitative descriptive statistics. The result of this research showed that (1) IIA grade students' reading poetry ability of SDN 1 Karangsari, Banyuwangi, included in enough categories. The percentage of IIA grade students' reading poetry ability based on the percentage calculation result of reading poetry ability was (a) 1 student was included in very good category with the percentage 4,54%; (b) 4 students were included in good category with the percentage 18,18%; (c) 14 students were included in enough category with the percentage 63,64%; (d) 3 students were included in less category with the percentage 13,64%, and (2) there were two kinds of factor that affect it, (a) internal factors were from students' them-selves, as like students’ interest, talent, motivation, self confidence, fear, rush, reading fluency, and student focus, dan (b) external factors consisted of the school environment and family. Key words: reading poetry ability, factors, new normal era.